ENT 300: Case Study : Vida Magnificence / Dzulqarnain Abdul Hakim - Abdul Hakim, Dzulqarnain (2021)
Essentially, this contextual investigation is about the foundation of Dato Dr. Hasmiza Othman or known as Dato Vida. She is the proprietor of Vida Magnificence Organization. Dato Vida has delivers a great deal of magnificence and wellbeing items. Vida Magnificence is a notable organization. For this situation study, I might want to share about the business person and a couple of things that everybody should think about Dato Vida and Vida Excellence Sdn. Bhd. There are numerous difficulties that Dato Vida needs to look before become a fruitful business person. Notwithstanding, every one of the accomplishments by Dato Vida can be incredible models and aides for individuals who likes to begin their business.